Discrepancy in Public Administration Services Due to Vacancy in Regional Head Positions - Tubagus Rekayasa Kamal Djunaedi; Faisal Santiago (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Vacancies in the position of regional heads have a significant impact on public services in the regions, which have implications for access, quality and responsiveness of services to the community. This study aims to identify and analyze the impact of vacancies of regional head positions on the delivery of public services and formulate strategies that can be done to improve the quality and responsiveness of public services in the regions. The research method used is normative legal research, with a focus on analyzing legal norms written in legislation and relevant legal literature. This approach is carried out by studying various regulations relating to public services and the authority of regional heads. The results showed that the vacancy of the regional head position caused serious disruption in the delivery of public services. This has resulted in a decline in service quality, delays in decision-making, and policy uncertainty that has a negative impact on public satisfaction. In addition, the vacancy poses challenges in maintaining public trust in the government. This research emphasizes the need for the transformation of public administration services to overcome the problems arising from the vacancy of the regional head position. Innovation and the use of information technology are expected to improve service efficiency and transparency. Recommendations are also given to develop human resource capacity and analyze community needs.